2016
DOI: 10.1103/physrevb.94.161105
|View full text |Cite
|
Sign up to set email alerts
|

Anion effects on electronic structure and electrodynamic properties of the Mott insulatorκ(BEDTTTF)2Ag2(CN)3

Abstract: The Mott insulator κ-(BEDT-TTF)2Ag2(CN)3 forms a highly-frustrated triangular lattice of S = 1/2 dimers with a possible quantum-spin-liquid state. Our experimental and numerical studies reveal the emergence of a slight charge imbalance between crystallographically inequivalent sites, relaxor dielectric response and hopping dc transport. In a broader perspective we conclude that the universal properties of strongly-correlated charge-transfer salts with spin liquid state are an anion-supported valence band and c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(90 citation statements)
references
References 48 publications
4
86
0
Order By: Relevance
“…32,34 These findings provide evidence that the metal-insulator transition observed in κ-(BEDT-TTF) 2 Hg(SCN) 2 Br at 80 K is not due to static charge ordering. Recent measurements of the Raman spectra as a function of temperature support this conclusion: no indications of charge imbalance has been observed 35 as the metal-insulator transition is passed.…”
Section: Infrared-active Molecular Vibrationsmentioning
confidence: 64%
“…32,34 These findings provide evidence that the metal-insulator transition observed in κ-(BEDT-TTF) 2 Hg(SCN) 2 Br at 80 K is not due to static charge ordering. Recent measurements of the Raman spectra as a function of temperature support this conclusion: no indications of charge imbalance has been observed 35 as the metal-insulator transition is passed.…”
Section: Infrared-active Molecular Vibrationsmentioning
confidence: 64%
“…In addition, it has been suggested that the cation-anion interaction plays an important role in realizing the QSL state in the κ-type ET salts [29][30][31]. Therefore, we discuss the cation-anion interaction in the β -Pd(dmit) 2 salts, especially the S· · · H-C short contacts between the terminal thioketone group of the Pd(dmit) 2 molecule and the hydrogen atom in the cation.…”
Section: Cation-anion Interactionsmentioning
confidence: 96%
“…The smallest J/J ∼ 0.3 belongs to κ-(ET) 2 B(CN) 4 , which exhibits quasi 1D (spin-liquid) behaviour down to T = 5 K [53]. The 2D spin-liquid candidates κ-(ET) 2 Cu 2 (CN) 3 [7,54] and κ-(ET) 2 Ag 2 (CN) 3 [9,55] have J/J ∼ 1 − 2, close to the triangular limit. The orientation of each DM-vector with respect to the ET molecules is shown in Fig.…”
mentioning
confidence: 88%